A comparative study of the efficiency of a pro-biotic and the anti-K99 and anti-A14 vaccines in the control of diarrhea in calves in Brazil. - Avila, F. A.; Paulillo, A. C.; Schocken-Iturrino, R. P.; Lucas, F. A.; Orgaz, A.; Quintana, J. L. (My University, 1995)
A total of 99 pregnant cows were divided into eight groups submitted to the following treatments: group I (n = 29) consisted of unvaccinated cows whose calves did not receive a probiotic and was used as control. Group II (n = 10) consisted of vaccinated cows whose calves did not receive a probiotic. Groups III, IV and V (n = 10 neach) consisted of vaccinated cows whose calves received a probiotic for 5, 15 and 30 days, respectively. Groups VI, VII and VIII (n = 10 each) consisted of unvaccinated cows whose calves received a probiotic for 5, 15 and 30 days, respectively. Each animal in the vaccinated groups received two 5.0 ml vaccine doses containing pili K99 and A14 of Escherichia coli by the subcutaneous route. The probiotic containing Lactobacillus acidophilus at the dose of 2.0 x 10(8) live cells in 250 ml milk, was administered orally. All animals were observed clinically and bacteriologically and anti-K99 and anti-A14 antibody titers were determined in serum and colostrum. Mean calf weight was measured at birth and at 30 days of age. The results showed that a combination of the vaccine with the probiotic administered for 15 and 30 days was the most efficient treatment for the control of diarrhea.
Keywords: bacterial vaccine; animal; animal disease; Brazil; cattle; cattle disease; comparative study; diarrhea; Escherichia coli; female; immunology; Lactobacillus acidophilus; microbiology; pregnancy; Animals; Bacterial Vaccines; Cattle; Cattle Diseases; Diarrhea; Female; Pregnancy